Dampak Pembelajaran Secara Daring di Madrasah Aliyah Al-karomah - Qamariyah Qamariyah; Mamluatur Rohmah; Kamal Yusuf (STAI Attanwir Bojonegoro, 2022)
This study aims to determine the problems faced by students during web-based learning, students' insight into the direction given by Islamic senior High School Al-Karomah, besides that this study aims to determine student assumptions in terms of internet learning at senior High School Al-Karomah, Pamekasan, Madura so that it can run more smoothly. The method used in this research is a descriptive qualitative method. The technique used in this study is by distributing questionnaires to respondents, the Department of Social Education (IPS) is 26 people and some of the educators who educate at the institution are 8 people, with a total of 36 people. All respondents who were distributed on Google forms, filling out the form took place for 6 days from 13-18 April 2022. The results of this study indicate that there are several impacts found in learning Arabic class XII online at Islamic senior High School Al-Karomah, including : 1). The material presented makes it difficult for students, and finally students have difficulty understanding the material, 2). Inadequate signal during the learning process, 3). limited use of Arabic learning media, 4). interest and inspiration of students, 5). accessible time, there must be additional time, 6). and a less stable learning climate, the teacher's strategy in conditioning the class is less stable.